Antacids, Altered Mental Status, and Milk-Alkali Syndrome. (30th December 2012) - Watson, Simon C.; Dellinger, Bonnie B.; Jennings, Katie; Scott, Lancer A.
Abstract : The frequency of milk-alkali syndrome decreased rapidly after the development of histamine-2 antagonists and proton pump inhibitors for the treatment of peptic ulcer disease; however, the availability and overconsumption of antacids and calcium supplements can still place patients at risk (D. P. Beall et al., 2006). Here we describe a patient who presented with altered mental status, hypercalcemia, metabolic alkalosis, and acute renal failure in the context of ingesting large amounts of antacids to control dyspepsia.